A Study of Error Analysis from Students’ Sentences in Writing - Rizki Ananda; Sofyan A. Gani; Rosnani Sahardin (Studies in English Language and Education, 2014)
This study was to investigate the types of  sentence errors and their frequency  made by  first grade students from  a high school in Banda Aceh in their writing  of English. The participants for  this study were 44 first graders chosen by random sampling. The research method used was quantitative as the data was analyzed with a statistical procedure. The data was  obtained  from written tests  for  a descriptive text entitled “My school” of 120-140 word length. This study found that three out of four sentence errors in the students’ writing were fragmented sentences whilst nearly a quarter of the errors were run-on or comma splice sentences. There were only a few  choppy sentence  errors and no  stringy sentence  errors. The data revealed five  types  of fragmented  sentences:  these were  the absence of  a  subject, the absence of  a  verb, the absence of  both  a  subject and  a  verb, the absence of  a verb in a dependent clause, and the absence of an independent clause.